Melia azedarach: A phytopharmacological review - V, Vishnukanta; Rana, AC. (Pharmacognosy Reviews)
Ayurveda is a traditional Indian medicinal system being practiced for thousands of years. Considerable research on pharmacognosy, chemistry, pharmacology and clinical therapeutics has been carried out on ayurvedic medicinal plants. Natural products, including plants, animals and minerals have been the basis of treatment of human diseases. The current accepted modern medicine or allopathy has gradually developed over the years by scientific and observational efforts of scientists. However, the basis of its development remains rooted in traditional medicine and therapies. . Melia azedarach Linn, commonly known as mahanimba belongs to family Meliaceae. It is large evergreen tree found throughout India and very similar to neem. Traditionally it is used as anthelmintic, antilithic diuretic, emmenagouge, astringent and stomachic. Varios scientific studies reported the analgesic, anticancer, antiviral, antimalarial, antibacterial, antifeedent and antifertility avtivity of this plant. So the objective of the present review is to highlight the phytochemical and pharmacological information of this plant.
Keywords: Ayurveda; Melia azedarac; emmengogue; anticancer; antifeedant activity